Experimental investigation of air flow through a discharge port - Sim, Jarell Jia zhi (Nanyang Technological University, 2021)
There are many applications that uses a compressor as their main device. It is important to optimize the performance of the system so that users such as business operators and engineers can perform tasks efficiently and effectively. Hence, studies on factors affecting the performance of a compressors are needed. The discharge chamber, which is one of the main parts in a compressor, consists of a discharge port and a reed valve which are used to control the discharge flow area and the pressure during a discharge process. Many computational models have been formulated to understand the effect on performance due to the discharge port shape and reed valve design. By designing an experimental setup for a test rig, experimental results for each design on the discharge port shape and reed valve can be obtained to further support the reliability of the analytical models. In this project, design and main components of the experimental setup were presented. The design of the experimental setup, design requirements and conditions were taken from International Organization of Standardization (ISO). Components of the setup were taken from past projects and sourced externally. The design of the test rig was produced based on recent and ongoing studies of analytical models.